Perancangan Hotspot Cerdas Berbasis Mikrotik Router Dan Web Server Mini PC Raspberry PI Pada Laboratorium Prodi sistem Komputer STMIK Asia Malang - Trilianto, Tria; Arifin, Samsul (P3M Politeknik Negeri Banjarmasin, 2018)
The aim of this research was to developed a computer network system based on router os and web server authentication embedded in a mini PC, user login authentication process applied to a router hotspot system combined with mini PC so it can produce a good management system or which can be called as smart hotspot. The intelligent hotspot which is built has the ability to perform user management and authentication. User management built into this intelligent hotspot system has the ability to define user authority, bandwidth limitation hierarchy, and limitations to sites and user-accessible content, the system is capable of detecting malware, phishing or pornographic content or sites. This capability is created by implementing and modifying firewall features in mikrotik OS. User authentication is built by incorporating hotspot features in the router OS as well as web server embedded in a Raspberry PI mini PC. User authentication is applied with two login process that is first login process by entering username and password with purpose to determine user permissions, then second login process in the form of question according to given user class. Questions given in the form of problems related to the subjects Prodi Computer Systems. The results obtained from the construction of this intelligent hotspot system is a hotspot system that can provide education for users and provide more convenience services for users and learning media courses Computer Network Administration at STMIK Asia Malang. Based on the test system that has been done some weaknesses to the authentication and limitation that have been made, but from the weakness in general can be concluded that the system can run quite well.